Gilberto Enrique Parada García. Ley formal y ley material. La ley penal y su codificación en la construcción del Estado colombiano, 1819-1837. (2016)
Even within the historiographical lacunae that exists for the years between the Independence and the Regeneration, the two decades between Bolívar’s final military triumphs in Gran Colombia and the War of the Supremes are understudied. Thus, Gilberto Enrique Parada García’s examination of the law and the development of the New Granada legal code during these years is a much needed study on politics and public life at the beginning of the republic. The book focuses on the history of the legal system in the early republic, specifically the juridical and historical context within which the Penal Code of 1837 was developed. The study engages with legal theory and legal studies while remaining grounded in social and political history. Parts of the study have been published as individual articles and here are placed in a broader, more informative, discussion.